Dreaming and the COVID-19 pandemic: a survey in a U.S. sample - Schredl, Michael; Bulkeley, Kelly (Dreaming, 2020)
This study analyzes the responses of 3,031 U.S. adults who, in early May of 2020, completed an online survey regarding their dreams and the COVID-19 outbreak. The results indicate that those people most strongly affected by the pandemic also reported the strongest effects on their dream life (heightened dream recall, more negatively toned dreams, and pandemic-related dreams). Pronounced negative effects of the pandemic on dreaming were also found to be more likely among women and people with higher levels of education. These findings support the notion that changes in the frequency, tone, and contents of dreaming can help identify specific people who may be most at risk for mental health problems during the COVID-19 outbreak. (PsycInfo Database Record (c) 2025 APA, all rights reserved)